Desafios da produção do arroz orgânico nos assentamentos do município de São Gabriel-RS - Zanon, João Silvano (2015)
This research addresses the organic rice production process in the settlements Madre Terra, Cristo Rei and Zambeze and the impacts that such production engenders in São Gabriel / RS. With the crisis of conventional production model and the environmental, social and economic, resulting from the intensive use of agrochemicals, is included in the company an efficient production model, it is the agroecological agriculture developed during the production of organic rice process. From the literature focused on the topic of interest, as the struggle for land in Brazil and Rio Grande do Sul, the agro-ecological production strategies and the production of organic rice, it was possible to grasp the organic production system in question. To meet the objectives of the investigation, which presents a qualitative approach, was developed through semi-structured interviews, which were conducted with family farmers and settlers technicians COPTEC and ATES. Finally, it is evident that the productive organization of organic rice requires active participation of the community and technicians during the production process, because the organic management requires manual and daily work, and also the constant search for techniques and technologies that best suit the reality of the place and the variety of cultivated rice, and this form of production builds relationships between society and nature, modifying the configuration of the territory, incorporating a form of organization and different life, creating a new agriculture and a new farmer .